Peningkatan Keterampilan Bisnis Melalui Workshop Kewirausahaan di SMKN 1 Surabaya - Jundulloh Al Furqoni (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
Globalization not only leads to rapid changes in the operating strategies and market competition of companies but also eliminates the boundaries of competition that are local and global. Entrepreneurship in the globalization era has an important role in career development, economic growth, and as a stimulator of innovation and creativity. Entrepreneurship education faces challenges in its implementation, such as the limitations of conventional curricula that focus on theoretical aspects rather than practical skills. Entrepreneurship workshops can be a way to improve practical skills, creative thinking, and develop their ideas and potential in preparing for future business challenges. This activity aims to improve the knowledge and practical skills in entrepreneurship of SMK Negeri 1 Surabaya students through workshops. In the realization of the workshop, the steps taken were observation of the Vice Principal for Student Affairs, preparation, and implementation of the workshop. The workshop was held on Thursday, May 25, 2023, starting at 8:00 a.m. and attended by 155 students of SMK Negeri 1 Surabaya, consisted of Entrepreneurship Education sessions by experienced business practitioners, Focus Group Discussion (FGD) on Brand Positioning and Marketing Video Competition themed "Marketing & Advertising Campaign”. This workshop successfully created a holistic entrepreneurial learning environment by combining theoretical and practical aspects by providing knowledge related to business creation steps, application of branding positioning concepts, and practical skills in making marketing campaign videos. This workshop is expected to be a foundation for developing students' entrepreneurial skills and creativity in the future.